Analysis of a gas station hybridization with a solar thermal plant by using ETAP - Ahmed Zkear Abass; D. A. Pavlyuchenko (Institute of Advanced Engineering and Science, 2021)
Iraq is facing deficiency of electric power for last decades. The main reason for deficiency of electric power is due to less respect of analytical load flow studies of electric supply substation. To stop and overcome such situation in future, researchers should be analyzing different power substation focusing on load flow studies, short circuit studies and protection schemes. Due to lack of research and studies on load flow and fault analysis, Iraq is facing a lot of issues, such as power failures and high copper losses, solving of these problems on substation level, demand a high familiarity about the power system. In this paper we analyses combined typical gas station with solar thermal power station and survey load flow, short circuit, transient stability, and voltage drop before and after combined station by using electrical transient analyzer program (ETAP). Now a day’s power supply reliability and goodness are big interest. analyses of power system are a main part in power system designing and planning, in order to accommodate future loads and the expansion of cities.